Influencia de la temperatura de austenizacion en el rango de 820°c y 980°c sobre la templabilidad en una fundicion gris perlitica - Florián Huamán, Favio Rafael Junior. (2018)
In the present investigation we studied the influence of the austenitization temperature on the tempering of a pearlitic gray cast iron was studied. For this purpose, bars of 30 mm diameter x 400 mm length were used; of which the test specimens were machined for the test. Length of 25 mm in diameter and 100 mm in length. Said test was carried out according to the ASTM A255-2014 standard and to evaluate the U or Grossmann curve, it used probes of 25 mm diameter x 50 mm in length. The test pieces were heated to the austenitization temperatures of 820, 860, 900, 940 and 980 ° C for a time of 1 hour, the Jominy test was carried out in quenching device for tests, according to ASTM A255 - 2014, and for the evaluation of the curve U the test pieces were tempered in oil. The results show that the austenitization temperature increases from 820 ° C to 900 ° C, the templering increases when the temperatures are 940 ° C and the tempering decreases 980 ° C. It also shows that the gray cast iron in the study has a quenching y due to that the durability decreases rapidly at a small distance from the tempered end. Because of this, the austenitization temperature of 900 ° C is the appropriate temple temperature because at this foundry temperature under study it has the highest hardenability. According to the microstructural analysis, all the test pieces have graphite flakes that are stable and do not change with temperature.